HISTOPATHOLOGICAL CHANGES OF SCHISTOSOMIASIS FROM NAPU VALLEY, CENTRAL SULAWESI, 1NDONESIA - Kurniasih Kurniasih (Jurnal Sain Veteriner, 1998)
Schistosomiasis is an endemic disease caused by the infection Schistosoma Japonicum (Trematoda), can attack human and animals surrounding Lindu lake and Napu valley. Central Sulawesi, Indonesia. Five mice were naturally infected through subcuian with 75 cercariae of Schistosoma japonicum emerged from snail, Oncomelanic hupensis lindoensis, which were found in the Napu valley, Central Sulawesi. Mice showed a weakness, anorrhexia, stomach ache,and died in the fifth, sixth and seventh week posiinfection. At autopsy, mice had ascites, yellowish nodules on the surface of lung, liver, serosa of the small intestine, and mesenterium. Histolagically, there were severe necrosis and the granolomatous inflammation of the liver, the spleen, the lung, the pancreas, and the small intestine.